2021
DOI: 10.1007/978-3-030-80387-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Malicious and Low Credibility URLs on Twitter During the AstraZeneca COVID-19 Vaccine Development

Abstract: This study provides an in-depth analysis of a Twitter dataset around AstraZeneca COVID vaccine development released as a part of Grand Challenge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Also natural language processing techniques ( Sahingoz et al., 2019 ) and Shannon’s entropy ( Verma and Das, 2017 ) are used to determine the maliciousness of a URL. At last, a case study on Twitter data explores the malicious and inconsistent URLs during Covid-19 to identify link-sharing patterns ( Horawalavithana et al., 2021 ). The author suggests improving topic moderation techniques on Twitter data that mitigate the intent of poor players in promoting malicious activities.…”
Section: Related Workmentioning
confidence: 99%
“…Also natural language processing techniques ( Sahingoz et al., 2019 ) and Shannon’s entropy ( Verma and Das, 2017 ) are used to determine the maliciousness of a URL. At last, a case study on Twitter data explores the malicious and inconsistent URLs during Covid-19 to identify link-sharing patterns ( Horawalavithana et al., 2021 ). The author suggests improving topic moderation techniques on Twitter data that mitigate the intent of poor players in promoting malicious activities.…”
Section: Related Workmentioning
confidence: 99%
“…These external websites shared are often along ideological or political lines on social media platforms like Twitter Kuzma et al (2021) and have been observed to share deceptive content in a coordinated manner (i.e., during the 2019 European elections (Pierri et al 2020)). External websites have also shown to be an important part of misinformation-laden conversations like the Twitter discourse around the COVID-19 vaccination and are often used to spread misinformation (Cruickshank et al 2021;Horawalavithana et al 2021). Additionally, YouTube videos have been heavily spread on social media platforms and used in a wide range of mis/ disinformation campaigns.…”
Section: Related Workmentioning
confidence: 99%
“…Analysis of link sharing behavior has also given rise to observations of coordinated link sharing behavior. Recent work highlights that mis/disinformation campaigns not only spread external websites on social media platforms but also do so in a coordinated manner (Pacheco et al 2021;Horawalavithana et al 2021;Giglietto et al 2020). This coordinated link sharing behavior further spreads the mis/disinformation on the external website by getting the website to trend higher on the social media platform and hence artificially boosting its popularity (Giglietto et al 2020).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation